PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP MINAT PELANGGAN PADA BENGKEL JIHAN PRODUCT - Wibowo, Wahyu Tri; Winarso, Widi; Kurniawan, Dody; Nursal, M.Fadhli; Handayani, Milda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of service quality and location on customer interest at Jihan Product Workshop. In the face of an increasingly competitive workshop industry, improving service quality and selecting the right location have become crucial factors in retaining and attracting customers. The research adopts a quantitative approach with a descriptive method. Primary data was collected through questionnaires distributed to 117 respondents. Data analysis was carried out using the Partial Least Square (PLS) Method With The Help Of SmartPLS version 4.0. The results of the analysis show that both service quality and location have a positive and significant effect on customer interest. These findings indicate that optimal service and a strategic workshop location can increase customers’ interest in using the service offered by Jihan Product Workshop.